Fullerene C60 reduces acute lung injury by suppressing oxidative stress-mediated DMBA-induced apoptosis and autophagy by regulation of cytochrome-C/caspase-3/beclin-1/IL-1?/HO-1/p53 signaling pathways in rats - Beyaz, Seda; Aslan, Abdullah; Gok, Ozlem; Ozercan, Ibrahim Hanifi; Agca, Can Ali (Taylor & Francis Ltd, 2023)
The objective of this study was to evaluate the effect of fullerene C-60 nanoparticles against 7,12-dimethylbenz[a]anthracene (DMBA)-induced lung tissue damage in rats. 60 Wistar albino (8 weeks old) female rats were assigned into four groups: Control Group (C), Fullerene C-60, DMBA, and Fullerene C-60+DMBA. The rats in the DMBA and Fullerene C60+DMBA groups were administered DMBA (45 mg/kg bw, oral gavage). The rats in Fullerene C-60, and Fullerene C-60+DMBA groups were administered with Fullerene C-60 (1.7 mg/kg bw, oral gavage). Expression levels of cytochrome-C, caspase-3, beclin-1, IL-1 alpha, HO-1 and p53 proteins in lung tissue were determined by western blotting, lipid peroxidation malondialdehyde (MDA) analyzes, glutathione (GSH), glutathione peroxidase (GSH-Px), catalase activity (CAT) and total protein levels were determined by spectrophotometer. In addition, lung tissues were evaluated by histopathologically. Fullerene C-60 reduced the increasing of MDA and IL-1 alpha protein expression levels and attenuated histopathological changes in lung. Moreover, fullerene C-60 enhanced the protein expression of cytochrome-C, caspase-3, beclin-1, HO-1, and p53, which were decreased in the DMBA group. Fullerene C60 has strong biological activity that it might be an effective approach for lung damage.
Keywords: Fullerene C-60; dMBA; lung; apoptosis; autophagy